La nueva prueba en el recurso de reconsideración: reflexiones desde la autotutela administrativa - Méndez Vásquez, Diego Enrique (2024)
The purpose of this paper is to clarify, based on the nature of the nullity processes in administrative appeals, the apparent conflict that arises when interpreting the effects of the new evidence in reconsideration appeals. To do so, two key issues are addressed: the object of administrative appeals and the evidentiary activity in administrative proceedings. The analysis of these issues allows us to reach an adequate and systematic interpretation that defines the scope of the new evidence.